Self-reports of Cognitive Vulnerabilities for Anxiety Suggest Escalating Severity across Adult Age Ranges: A Cross-sectional Investigation. Issue 1 (April 2016) - Fetzner, Mathew G.; Horswill, Samantha A.; Carleton, R. Nicholas
Cognitive vulnerabilities have been posited as central to the development of anxiety disorders and have been given substantial research attention. Despite widespread empirical investigations into the relationships with symptoms of mental disorders, and use as markers of symptom severity among clinical adult populations, research is lacking information on the progression of cognitive vulnerabilities across adulthood. The investments associated with longitudinal research requires a priori evidence of age-related differences from cross-sectional data. The current research used 1477 community members (72% female, 18–64 years) to cross-sectionally assess trends in cognitive vulnerabilities and their dimensions throughout adulthood and between distinct age groups (i.e., 18–19, 20–29, 30–39, 40–49, and 50+). Results suggest small, albeit statistically significant, associations with age which provide important insight into construct stability across adulthood and potentiate an avenue towards the understanding of progression across adulthood. Vulnerabilities encompassing somatic symptoms (i.e., fear of physiological sensations, injury, and illness) and uncertainty over future events (i.e., prospective-IU) exhibited positive linear relationships with age. Vulnerabilities encompassing fears of evaluation (i.e., fear of negative evaluation and socially observable anxiety), behavioral inhibition (i.e., inhibitory-IU), and loss of cognitive control (i.e., fear of cognitive dyscontrol) exhibited quadratic relationships with age. Participants over 50 years of age tended to report elevated cognitive vulnerabilities. Comprehensive results and directions for future research are discussed.